Evolution of Fagan's Nomogram; a Commentary - Abdelrahman Ibrahim Abushouk (Archives of Academic Emergency Medicine, 2018)
I read with interest your paper entitled "Pre and post-test probabilities and Fagan’s nomogram. I would like to add a note concerning an update on Fagan’s Nomogram. In 2011, a group of researchers published a modern version of the nomogram that they named "Bayes’ theorem nomogram".